Rola asystenta rodziny we wspieraniu rodzin z ograniczonymi prawami rodzicielskimi - Rajewska de Mezer, Joanna (Studia Edukacyjne, 2018)
With its specific way of functioning and network of interweaving interactions of various character and emotional intensity, the family is an environment where the process of a child’s socialization takes place, social personality develops and patterns of social roles are acquired. A family that malfunctions can trigger deviation mechanisms, thus considerably contributing to a child’s social maladjustment. Due to that, in case the criteria described by law are met, it is necessary to use specific assistance measures and interfere in a family’s autonomy, limit its parental authority and support it in fulfilling educational and socialization functions. Appointing a family assistant is one of the measures of limiting parental authority aimed at helping a family.